Ethics with an economic method: A new perspective on business ethics - Petrus Naude (AOSIS, 2021)
Purpose: The purpose of this article was to review the book of Christoph Lütge and Matthias Uhl (2021) entitled Business ethics. An economically informed perspective (Oxford University Press).